Xamarin cross-platform mobile application development : master the skills required to develop cross-platform applications from drawing board to app store(s) using Xamarin : a course in three modules.: master the skills required to develop cross-platform applications from drawing board to app store(s) using Xamarin : a course in three modules. (2016) - Unknown
No abstract available